Automated ingredient mixer machine / Aiman Shafiq Zainudin - Zainudin, Aiman Shafiq (2023)
At Jalen Sdn. Bhd. factory, the ingredient mixing process was done manually. The worker will start by pouring out all the ingredient into a mixing bowl and the other operator will be started to mix the ingredient until it achieves the wanted product. In this era, manual process will delay the production time and can consume a lot of manpower to complete some process. To solve this problem, an Automated Ingredient Mixing and Dispenser Machine is created. The main objective for this project is to reduce the manpower needed in the production process by making a machine that is simple to be operated. The study for the mixing machine includes some theories and principles that will be used in the making for the mixing machine. This machine will work with a dispenser that dispense the ingredient automatically. Then, the ingredient will flow through a modified funnel to the mixer machine that will automatically mix the ingredient until it mixed well. This study will be matched accordingly to satisfy the main objective. The result from this project are the number of operator is reduced to only 1 person to operate the machine. As this machine can help the to complete the process of mixing, dispensing, and carrying the ingredients to the next process, there were no need for another operator to divide their work. Moreover, the time are also reduced to 30 minutes per batch production. This is due to the action where the machine minimized the process of mixing, dispensing, and carrying the ingredients to the next part where the manual method before taking a duration of 1 hour per batch production. Thus, the automated ingredient mixing, and dispenser machine can solve the problem that faced by Jalen Sdn. Bhd. and can increase the efficiency of the process hence, increasing the production rate